Report of the Inter-agency Task Force on Financing for Development 2018 - United Nations Department of Economic; Social Affairs (United Nations, 2018)
The Inter-agency Task Force Report assesses progress in the seven action areas of the Addis Ababa Action Agenda: (i) domestic public resources; (ii) domestic and international private business and finance; (iii) international development cooperation; (iv) international trade as an engine for development; (v) debt sustainability; (vi) addressing systemic issues; and (vii) science, technology, innovation and capacity building. The 2018 edition focuses on investments in water, energy, ecosystems, and cities in particular. The report primarily targets Member States, particularly policymakers from ministries of finance, trade, foreign affairs and development cooperation, as well as central banks, local authorities, regulators and parliaments.